Surgical Techniques and Outcomes in Patients With Intra-Cardiac Abscesses Complicating Infective Endocarditis - Straw, Sam; Baig, M. Wazir; Mishra, Vishal; Gillott, Richard; Witte, Klaus K.; Van Doorn, Carin; Ferrara, Antonella; Javangula, Kalyana; Sandoe, Jonathan A. T. (Frontiers in Cardiovascular Medicine, 2022)
Background Intra-cardiac abscess is a serious complication of both native (NV-IE) and prosthetic valve infective endocarditis (PV-IE). Despite being an accepted indication for surgery, controversies remain regarding the optimal timing and type of operation. We aimed to report the outcomes of patients managed for intra-cardiac abscesses over more than a decade. Methods Patients aged 18 years managed for intra-cardiac abscess between 01/01/2005 and 31/12/2017 were identified from a prospectively collected IE database. The primary outcome was 30-day mortality in operated patients and secondary outcomes were freedom from re-infection, re-operation and long-term mortality comparing those patients with aortic root abscess who underwent aortic valve replacement (AVR) and those who received aortic root replacement (ARR). Results Fifty-nine patients developed intra-cardiac abscess and their median age was 55 (43-71) years, 44 (75%) were male and 10 (17%) were persons who inject drugs. Infection with beta-haemolytic streptococci was associated with NV-IE (p=0.009) and coagulase negative staphylococci with PV-IE (p=0.005). Forty-four (75%) underwent operation, and of those with aortic root abscess, 27 underwent AVR and 12 ARR. 30-day mortality was associated with infection with S. aureus (p=0.006) but not type or timing of operation. Survival in operated patients was 66% at 1-year and 59% at 5-years. In operated patients none had relapse, although six developed late recurrence. Freedom from infection, re-operation and long-term mortality were similar in patients undergoing AVR compared to ARR. Conclusions Patients with intra-cardiac abscesses who were not operated on had very poor survival. In those who had surgery, undertaking AVR or ARR based upon patient factors, imaging and intra-operative findings resulted in similar outcomes.